Prognostic Impact of Low-Level p53 Expression on Brain Astrocytomas Immunopositive for Epidermal Growth Factor Receptor - Hung-Pei Tsai; Chien-Ju Lin; Chieh-Hsin Wu; Yi-Ting Chen; Ying-Yi Lu; Aij-Lie Kwan; Ann-Shung Lieu (Current Issues in Molecular Biology, 2022)
Although the expression of p53 and epidermal growth factor receptor (EGFR) is associated with therapeutic resistance and patient outcomes in many malignancies, the relationship in astrocytomas is unclear. This study aims to correlate p53 and EGFR expression in brain astrocytomas with overall patient survival. Eighty-two patients with astrocytomas were enrolled in the study. Semi-quantitative p53 and EGFR immunohistochemical staining was measured in tumor specimens. The mean follow-up after astrocytoma surgery was 18.46 months. The overall survival rate was 83%. Survival was reduced in EGFR-positive patients compared with survival in EGFR-negative patients (p < 0.05). However, no significant differences in survival were detected between patients with high and low p53 expression. In patients with low p53 expression, positive EGFR staining was associated with significantly worse survival compared with patients with negative EGFR staining (log-rank test: p < 0.001). Survival rates in positive and negative EGFR groups with high p53 protein expression were similar (log-rank test: p = 0.919). The IC50 of an EGFR inhibitor was higher in GBM cells with high p53 protein expression compared with the IC50 in cells with low p53 expression. Combined EGFR and p53 expression may have prognostic significance in astrocytomas.